Analisis Penilaian Kinerja Ekonomi Daerah Provinsi DKI Jakarta Periode Tahun 2019-2023 - Eko Saputra; Abdul Aziz Ahmad (Fakultas Ekonomi Universitas 45 Surabaya, 2025)
Regional economic development is a crucial aspect in determining the welfare level of society and the economic growth of a region. This study aims to analyze the economic performance of DKI Jakarta Province from 2019 to 2023 using the Location Quotient (LQ), Dynamic Location Quotient (DLQ), and a combined LQ-DLQ model to identify leading and potential economic sectors. This research adopts a quantitative approach using secondary data, including the Gross Regional Domestic Product (GRDP) of DKI Jakarta and the Gross Domestic Product (GDP) of Indonesia. The findings indicate that the financial services, real estate, and information and communication sectors are classified as base sectors with LQ > 1, signifying a comparative advantage over the national level. Meanwhile, the transportation and warehousing sector has a DLQ > 0 but LQ < 1, indicating growth potential for the future. On the other hand, the manufacturing, mining, and electricity & gas supply sectors have LQ < 1 and DLQ < 0, suggesting that these sectors lack competitiveness in DKI Jakarta.These results indicate that strengthening the service sector as the primary driver of DKI Jakarta’s economy must be continuously promoted through innovation, investment, and strategic policies. Additionally, specific policies are needed to develop potential sectors, such as transportation and warehousing, to enhance regional economic competitiveness. Thus, this study is expected to provide recommendations for local governments in formulating sustainable economic development strategies.